THE STUDY OF PREVALENCE OF PREMENSTRUAL SYNDROME AMONG NURSING AND PARAMEDICAL STUDENTS AND ITS IMPACT ON ACADEMIC AND QUALITY OF LIFE, S V MEDICAL COLLEGE, TIRUPATI, SOUTH INDIA - KALYANI, VANKEEPURAM VISHNU; ARUNA, Y.; BHUVANESWARI (International Journal of Current Pharmaceutical Research, 2025)
Objective: The term premenstrual syndrome (PMS) describes a group of upsetting symptoms that occur around the time of menstruation. These symptoms may be caused by hormonal changes, which can impair daily functioning and quality of life. Methods: In this cross-sectional study, 165 Nursing and Paramedical students who were unmarried and having regular menstrual cycles in last 6 mo and those who are willing to give written informed consent are included. A self-reported questionnaire containing 3 parts covering all aspects was used. PMS is diagnosed (ACOG criteria) if at least one of the 6 affective symptoms and one of the somatic symptoms were reported 5 d prior to menstrual cycles and ceased within four days of onset of menses. Results: The prevalence of PMS was 62.7%. Back, joint and muscle aches were the most common symptoms, followed by abdominal heaviness and discomfort. PMS was associated with a poorer quality of life across all domains. About half the students had affective symptoms in the premenstrual phase. Conclusion: PMS symptoms significantly affect women's well-being and overall quality of life. Dietary and lifestyle factors such as consumption of sweets and lack of physical activity were associated with the presence of PMS.